PROFIL TINGKAT KECEMASAN BELAJAR KIMIA SISWA KELAS XII IPA SEMESTER 1 PADA SMA NEGERI DI KABUPATEN KLATEN - Rahmawati, Linda Azizah; Aloysius, Heru Pratomo (Jurnal Riset Pembelajaran Kimia, 2024)
Difficulties and failures in learning chemistry can lead to chemophobia or chemistry learning anxiety among students.. This study aims to measure the level of learning anxiety among 12th-grade science students in the odd semester of chemistry learning. This is a non-intervention quantitative study using a survey method. The result showed that the average level of learning anxiety among 12th-grade science students in the odd semester of chemistry learning was in the low category. Specifically, the distribution of anxiety levels is as follows: very high (2,63%); high (9,63%); moderately anxious (20,57%); low (42,01%); and very low (25,16%). These findings indicate that although a small portion of students experience high anxiety, the majority of students have a low level of anxiety in learning chemistry. These findings can serve as a basis of designing more effective teaching strategies to reduce anxiety about learning chemistry among students.